AUTIZM SPEKTRIDA BUZILISHI BOʻLGAN BOLALARNING PSIXOLOGIK XUSUSIYATLARI - Vapoyeva, R.R. (SCIENCE and SOCIETY, 2025)
The article lists psychological characteristics of children with autism spectrum disorders, their study by psychologists from abroad and Uzbekistan, analysis of clinical signs and socio-psychological characteristics and methodology determining the level of intelligence based on schemes and tables.